Development of energy efficient design proposals for air conditioned mosques: Temperate humid climate case - Atmaca, A. B.; Gedik, G. Zorer (CELL PRESS, 2023)
Mosques, which are types of religious buildings, are large buildings where many people pray at the same time. The diversity of the user type and density and the variability of the usage schedule make it difficult to establish the homogeneous thermal comfort of these large-volume public buildings. At the same time, the energy consumption in the buildings should be minimal in nowadays when the conventional energy sources decrease. The aim of this study is to evaluate created design strategies for designers and users in order to minimize energy consumption by determining the passive design criteria and choosing the type of air conditioning equipment while providing an acceptable thermal comfort level in mosques. According to the method created for the aim, the scenarios of mosques were compared in terms of thermal comfort and energy consumption in the temperate humid climate conditions. This method includes the analysis of scenarios created from the change of design parameters of mosques (plan, size, roof type of the mosques) with a simulation software which was validated with actual utility data. The suggestions were presented for the selection and design of the mechanical system as a result of the implementation of the created method. When the design scenarios of mosques are compared, the air conditioning of the indoor with radiant method consumed less energy than HVAC equipment with fan system. In accordance with the plan schemes (square, rectangle, circular), the least energy consumption per unit area was in the circular plan scheme and hemispherical design. Compared to the roof types (single dome, multi dome, pyramidal roof, flat roof), the most energy consumption per unit area was generally in the multi dome design. According to the average energy consumption values of the HVAC systems, there was 23 % less energy consumption in the flat plan type (105.06 kWh/m2) compared to the rectangular plan type (129.2 kWh/m2). In the intermittent use schedule of the HVAC system, 8 % more energy was consumed than in the continuous use schedule. According to the air changes per hour in the mosques, there was 5.93 % more energy consumption in 2 ach conditions compared to 0.5 ach conditions.
Keywords: Thermal comfort; Energy consumption; Mosque; Building design; ENVELOPE THERMAL DESIGN; COMFORT; BUILDINGS; HOT; CONSUMPTION; OCCUPANCY; SYSTEM; Science & Technology - Other Topics